Peran Dukungan Teman Sebaya Dalam Pembentukan Rasa Percaya Diri Remaja Di MAN 2 Medan - Ainul Mardiyah; Nadine Khalifi Ermawan; Syifa Aulia; Haikal Mubarok Marpaung (CV. SINAR HOWUHOWU, 2025)
This study aims to describe and analyze the role of peer support in shaping the self- confidence of adolescents at MAN 2 Medan. Using a descriptive qualitative approach, data were collected through semi-structured interviews with several purposively selected students. The findings indicate that peer support plays a significant role in enhancing adolescents' self- confidence through various forms of support, such as appreciation of opinions, social acceptance, encouragement, and positive group interactions. Adolescents who receive higher levels of peer support show greater courage, openness, and self-assurance compared to those with lower support. The study also reveals that peer support becomes more effective when reinforced by other factors such as parental support, a conducive school environment, and adolescents' selectivity in choosing friends. Therefore, it can be concluded that peer support is an essential social factor that contributes to the development and strengthening of adolescents' self-confidence.